Weather - Chanko, Pamela, 1968-; Moreton, Daniel (New York : Scholastic, 1998)
Photographs and simple text describe some of the activities associated with various types of weather, from ice skating to going to the beach.
1.0
K-3
Keywords: Weather -- Juvenile literature; Weather; Weather